Slovenski verz od srednjega veka do Prešerna - Bjelčevič, Aleksander (Jezik in slovstvo, 2020)
The article presents the metrical and strophic repertoire, the rhythm and rhyme of religious songs from the Middle Ages to the end of the eighteenth century, addressing the Latin and German origins of this repertoire, the internationality of church songs, the gradual transformation from syllabic verse to accentual-syllabic, and the influence on the strophic repertoire of secular songs from Janez Dev to France Prešeren (from the second half of the eighteenth century to first half of the nineteenth century). Over the centuries, church songs have created dozens of stanzaic types, some very complex, and only the most common and simplest types have come into folk and secular song, such as long metre, Romanzenstrophe, stabat mater stanza and Hildebrand's stanza.
Keywords: accentual-syllabic verse; cerkvena pesem; church song; kitica; rhyme; rhythm; rima; ritem; silabizem; silabotonizem; stanza; syllabic verse; verzifikacijski sistem